For Farmers or the Environment? The European Parliament in the 2013 CAP Reform - Gravey, Viviane (2021)
The Common Agricultural Policy (CAP) was the last policy field to be placed under the Ordinary Legislative Procedure and its 2013 reform was the first to be decided under this rule. This article analyses how rule changes following the Lisbon Treaty have shaped policy outcomes related to ‘greening,’ i.e., making agricultural policy more environmentally friendly. Measuring the policy ambitions of amendments during the different phases of the legislative process (the processing phase within the Parliament and the negotiating phase during trilogues), we find that the European Parliament weakened the Commission’s greening proposals—but did so to support an alternative greening agenda built on different policy instruments. This means that rule change has altered the power balance between the institutions, making the Commission more dependent on the European Parliament. In the 2013 reform, this new balance of power came at the cost of greening the CAP.